A digital approach to fabricating a ceramic crown to fit an existing denture: Pendekatan digital untuk membuat mahkota keramik agar sesuai dengan gigi tiruan - Eri Hendra Jubhari; Nurul Ekayanti Udinsiah (Makassar Dental Journal PDGI Makassar, 2021)
A fixed restoration is required for improvement of function, comfort and esthetics, although the manufacturing technique is not easy. In this digital era, various tools have been developed to facilitate the manufacture of dentures, whether complete dentures, removable partial dentures or fixed dentures or fixed restorations. Computer-aided design/computer-aided manufac-turing (CAD/CAM) is a technology that has been developed in the world of dentistry to make it easier for dentists and labo-ratory technicians to work on prostheses, reduce the number of treatment visits and the results are better; although there are drawbacks, namely the cost is not cheap. Ceramics are one of the most esthetic prosthetic materials and resemble natural teeth so that it is in great demand, while zirconia is a material known for its excellent strength and esthetics so it is used as a core material. Zirconia has been known in the field of dentistry for several years and can be used as an ingredient in CAD/ CAM technology.